Over-Inclusive Gang Enforcement and Urban Resistance: A Comparison Between Two Cities - Durán, Robert (Social justice, 2009)
A study examined the responses of gang members in the Mexican-American barrios of Denver, Colorado, and Ogden, Utah, to the enforcement tactics created in the post-Civil Rights era. Data were obtained from give years of research between 2001 and 2006, involving interviews with gang members and observations police interactions with gang members. Findings indicated that in the post-Civil Rights era, the most frequent response of barrio residents to police actions was accommodation, as they recognized that they would not be treated in a fair manner and their complaints of mistreatment were described as unfounded. Findings suggested, however, that a history of Chicano activism in Denver made resistance an integral part of the barrio experience, although Ogden remained silent in the face of overwhelming overt and covert racism and religious prosecution. Findings are discussed in detail.